Prevention of Herpes Zoster and its complications: From clinical evidence to real life experience - Giovanni Gabutti; Paolo Bonanni; Michele Conversano; Guido Fanelli; Elisabetta Franco; Donato Greco; Giancarlo Icardi; Marzia Lazzari; Alessandro Rossi; Silvestro Scotti; Antonio Volpi (Taylor & Francis Group, 2017)
Herpes zoster (HZ) is an acute viral illness characterized by a vesicular rash with unilateral distribution, which can also result in severe complications such as post-herpetic neuralgia (PHN), ophthalmic zoster, stroke or other neurological complications. The estimate incidence in Europe ranges between 2.0 and 4.6 cases per 1,000 person-years, with a sharp increase in >50 year-old subjects. Currently, treatment options for HZ are only partially effective in limiting the acute phase, while the management of complications is complex and often unsatisfactory. The total burden of the disease and the high costs related to its diagnostic and therapeutic management led researchers to develop a new preventive approach through a live attenuated virus vaccine. The currently available vaccine, with a high antigen content, is safe, well tolerated and reduces the incidence of HZ, PHN and the burden of illness. Several countries have introduced this vaccination, albeit with different recommendations and methods of financing. Taking into account the barriers to this immunization registered in some areas (difficulty of vaccine distribution, lack of physician recommendations, the cost of vaccine for patients, etc.), this group of Italian experts advocate that a common strategy able to guarantee a good compliance with this vaccination should be implemented. The same group addresses some practical questions concerning the use of zoster vaccine.